Omission of Radiotherapy in Primary Mediastinal B-Cell Lymphoma: IELSG37 Trial Results - Martelli, Maurizio; Ceriani, Luca; Ciccone, Giovannino; Ricardi, Umberto; Kriachok, Iryna; Botto, Barbara; Balzarotti, Monica; Tucci, Alessandra; Usai, Sara Veronica; Zilioli, Vittorio Ruggero; Pennese, Elsa; Arcaini, Luca; et al. (Journal of clinical oncology, 2024)
PURPOSE: The role of consolidation radiotherapy in patients with primary mediastinal B-cell lymphoma (PMBCL) is controversial. METHODS: The IELSG37 trial, a randomized noninferiority study, aimed to assess whether irradiation can be omitted in patients with PMBCL with complete metabolic response (CMR) after induction immunochemotherapy. The primary end point was progression-free survival (PFS) at 30 months after random assignment. Patients with CMR were randomly assigned to observation or consolidation radiotherapy (30 Gy). With a noninferiority margin of 10% (assuming a 30-month PFS of 85% in both arms), a sample size of 540 patients was planned with 376 expected to be randomly assigned. RESULTS: The observed events were considerably lower than expected; therefore, primary end point analysis was conducted when ≥95% of patients were followed for ≥30 months. Of the 545 patients enrolled, 268 were in CMR after induction and were randomly assigned to observation (n = 132) or radiotherapy (n = 136). The 30-month PFS was 96.2% in the observation arm and 98.5% in the radiotherapy arm, with a stratified hazard ratio of 1.47 (95% CI, 0.34 to 6.28) and absolute risk difference of 0.68% (95% CI, -0.97 to 7.46). The 5-year overall survival (OS) was 99% in both arms. Nonrandomized patients were managed according to local policies. Radiotherapy was the only treatment in 86% of those with Deauville score (DS) 4 and in 57% of those with DS 5. The 5-year PFS and OS of patients with DS 4 (95.8% and 97.5%, respectively) were not significantly different from those of randomly assigned patients. Patients with DS5 had significantly poorer 5-year PFS and OS (60.3% and 74.6%, respectively). CONCLUSION: This study, the largest randomized trial of radiotherapy in PMBCL, demonstrated favorable outcomes in patients achieving CMR with no survival impairment for those omitting irradiation.
Keywords: Young Adult; Male; nádory mediastina; doba přežití bez progrese choroby; Antineoplastic Combined Chemotherapy Protocols; mladý dospělý; Lymphoma, B-Cell; Adult; B-buněčný lymfom; Aged; dospělí; mužské pohlaví; senioři; lidé; ženské pohlaví; Humans; protokoly protinádorové kombinované chemoterapie; Mediastinal Neoplasms; Female; Progression-Free Survival; lidé středního věku; Middle Aged